How do you solve #2- 3[ x - 2( x + 1) ] = x - [ 2- ( x - 3) ]#?

Answer 1

#x=-13#

We get #2-3(x-2x-2)=x-2(2-x+3)# #2-3(-x-2)=x-(5-x)# expanding
#2+3x+6=x-5+x#
#8+3x=2x-5#

and this is

#x=-13#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the equation (2 - 3[x - 2(x + 1)] = x - [2 - (x - 3)]), follow these steps:

  1. Distribute and simplify within each set of brackets.
  2. Combine like terms on each side of the equation.
  3. Isolate the variable (x) on one side of the equation.
  4. Solve for (x).

Starting with step 1:

(2 - 3[x - 2(x + 1)] = x - [2 - (x - 3)])

(= 2 - 3[x - 2x - 2] = x - [2 - x + 3])

(= 2 - 3[x - 2x - 2] = x - [5 - x])

(= 2 - 3[x - 2x - 2] = x - 5 + x)

Now, simplify further:

(2 - 3[x - 2x - 2] = 2x - 5)

(= 2 - 3[-x - 2] = 2x - 5)

(= 2 + 3x + 6 = 2x - 5)

Combine like terms:

(3x + 8 = 2x - 5)

Now, isolate the variable (x):

(3x - 2x = -5 - 8)

(x = -13)

So, the solution to the equation is (x = -13).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To solve the equation (2 - 3[x - 2(x + 1)] = x - [2 - (x - 3)]), follow these steps:

  1. Simplify the expressions within brackets.
  2. Apply the distributive property where necessary.
  3. Combine like terms.
  4. Solve for the variable (x).

Starting with the given equation:

[2 - 3[x - 2(x + 1)] = x - [2 - (x - 3)]]

[2 - 3[x - 2x - 2] = x - [2 - x + 3]]

[2 - 3[x - 2x - 2] = x - [5 - x]]

Now simplify inside the brackets:

[2 - 3[x - 2x - 2] = x - [5 - x]]

[2 - 3[-x - 2] = x - [5 - x]]

[2 + 3x + 6 = x - (5 - x)]

[8 + 3x = x - 5 + x]

[8 + 3x = 2x - 5]

Now, isolate (x) on one side:

[8 + 3x = 2x - 5]

[3x - 2x = -5 - 8]

[x = -13]

Therefore, the solution to the equation is (x = -13).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7